Superconducting Multilayer Technology for Josephson Devices : Technology, Engineering, Physics, Applications - Meckbach, Johannes Maximilian (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2013)
Within this book fabrication processes for high-quality Josephson junctions based on niobium and aluminum oxide as well as niobium nitride and aluminum nitride on various substrates are discussed. Techniques for achieving a planar chip topography and sub-µm lateral dimensions, aiding the realization of sophisticated Josephson devices such as SQUIDs, flux-flow oscillators and long Josephson junctions with artificial phase discontinuities, are presented in detail.